Palaces In The Historical Cities Of Uzbekistan Formation - Mahmudova Feruza Ibraimovna (Zien Journals, 2022)
In this article, on the basis of research and use of the evolution and architecture of the formation and development of palaces in Uzbekistan, the architecture of palace buildings and complexes occupies its leading position in the civilization of mankind, as an object of government that captivates the general public art, architecture in space and time, also because it reflects the high heights inherent in construction and folk applied art, the architecture of the palaces was informed about the wealth of the periods in which they were created and the future preservation of folk culture for the future generation.
Keywords: historical cities; architecture; embankments; lawns